2016
DOI: 10.1103/physreva.94.053636
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast coherent control of spinor Bose-Einstein condensates using stimulated Raman adiabatic passage

Abstract: We propose the use of stimulated Raman adiabatic passage (STIRAP) to offer a fast high fidelity method of performing SU(2) rotations on spinor Bose Einstein condensates (BEC). Past demonstrations of BEC optical control suffer from difficulties arising from collective enhancement of spontaneous emission and inefficient two-photon transitions originating from selection rules. We present here a novel scheme which allows for arbitrary coherent rotations of two-component BECs while overcoming these issues. Numerica… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…[31], it was shown that by a suitable choice of parameters it is possible to obtain gates in the range of ∼ MHz, which still exceed the gate speeds based on microwave pulses. An alternative method based on the stimulated Raman adiabatic passage (STIRAP) potentially offers a far more superior approach, as it involves dark states not involving the excited state at all [48]. By eliminating the excited state contribution this greatly suppresses the dephasing due to spontaneous emission, which is one of the main drawbacks of using optical methods to control BECs.…”
Section: Spontaneous Emissionmentioning
confidence: 99%
“…[31], it was shown that by a suitable choice of parameters it is possible to obtain gates in the range of ∼ MHz, which still exceed the gate speeds based on microwave pulses. An alternative method based on the stimulated Raman adiabatic passage (STIRAP) potentially offers a far more superior approach, as it involves dark states not involving the excited state at all [48]. By eliminating the excited state contribution this greatly suppresses the dephasing due to spontaneous emission, which is one of the main drawbacks of using optical methods to control BECs.…”
Section: Spontaneous Emissionmentioning
confidence: 99%
“…For instance, the control of the onset of self-trapping of a condensate in a periodically modulated double well has been demonstrated [15]. Also, SU(2) rotations on spinor condensates has been coherently controlled by stimulated Raman adiabatic passage [16]. In addition, there have been several experimental and theoretical successful implementations of quantum optimal control algorithms for BEC [17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, upon changing the relative phase of these amplitudes, it is possible to modify the nal yield. This interference between quantum transition amplitudes is the underlying principle of coherent control [15][16][17][18][19][20][21][22]. Here, we consider the role of the relative phase of the modulations on the transitions between nonlinear modes.…”
Section: Introductionmentioning
confidence: 99%